2021
DOI: 10.3390/ijms22115748
|View full text |Cite
|
Sign up to set email alerts
|

Isoprenoid Derivatives of Lysophosphatidylcholines Enhance Insulin and GLP-1 Secretion through Lipid-Binding GPCRs

Abstract: Insulin plays a significant role in carbohydrate homeostasis as the blood glucose lowering hormone. Glucose-induced insulin secretion (GSIS) is augmented by glucagon-like peptide (GLP-1), a gastrointestinal peptide released in response to ingesting nutriments. The secretion of insulin and GLP-1 is mediated by the binding of nutrients to G protein-coupled receptors (GPCRs) expressed by pancreatic β-cells and enteroendocrine cells, respectively. Therefore, insulin secretagogues and incretin mimetics currently se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…This was previously studied in our research groups and was proved in terms of anticancer properties [ 30 ]. It was previously shown that the conjugation with phospholipids is an effective method for increasing the biological properties of numerous natural compounds [ 31 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was previously studied in our research groups and was proved in terms of anticancer properties [ 30 ]. It was previously shown that the conjugation with phospholipids is an effective method for increasing the biological properties of numerous natural compounds [ 31 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the discrepancy may include different time treatments, cellular models, and species used. In addition, we have to consider that the biological characteristics of 2D-monolayered cell models are not identical to islets cells as, it is well known that cell-to-cell communication and spatial arrangement in the islets allow signal synchronization, leading to more effective insulin secretion [38]. In any case, although few epidemiological studies have been published, they all conclude that BPS is associated with an increased risk of type 2 diabetes [39,40].…”
Section: Bisphenolsmentioning
confidence: 99%
“…In fact, the direct or indirect effect of LPC and G2A or GPR4 is controversial. In addition, the LPC derivative also targeted four other G protein-coupled receptors, namely GPR40, GPR55, GPR119, and GPR120 [ 126 , 127 ]. Studies have indicated that the stimulatory effect of isoprenoid derivatives of LPC on Ca 2+ signaling in MIN6 cells was GPR40-, GPR55-, GPR119-, and GPR120-dependent [ 127 ].…”
Section: Lpc-related Receptor and Chronic Painmentioning
confidence: 99%
“…In addition, the LPC derivative also targeted four other G protein-coupled receptors, namely GPR40, GPR55, GPR119, and GPR120 [ 126 , 127 ]. Studies have indicated that the stimulatory effect of isoprenoid derivatives of LPC on Ca 2+ signaling in MIN6 cells was GPR40-, GPR55-, GPR119-, and GPR120-dependent [ 127 ]. GPR40/GPR55 has been implicated in inflammatory pain and neuropathic pain [ 128 , 129 ], but studies on LPC and these receptors in chronic pain are lacking.…”
Section: Lpc-related Receptor and Chronic Painmentioning
confidence: 99%